International Anatomical Sciences and Cell Biology Conference Singapore 26-29 Mei 2010 - Tengku Fatimah Murniwati, Tengku Muda (Pusat Pengajian Sains Perubatan, 2010)
Chronic Obstrudive Pulmonary disease (COPO) Is a majof health problem worldWide. lnftammatOI)' changes signify a clear indication In the earty pathological changes ol the airway In this dsease. Cigarette smoking Is the most oommon risk factor. Currently there Is no definitlve treatment to aKe the disease. Thus, the ultima1e goal is disease prevention. Recently, honey has been shown to have significant thefapeutic properties. The obje<:live of this study was to evalUate the effect or honey on the inftammatory process In the small airways of rats exposed to cigarette smoke. T_,ty three male rats aged eight to nine weeks old were randomly divided into lllf1le groups. Flr&t group was exposed daly to dgarette smoke atone using smolang apparatus. Seoond group was exposed to smoke and given oral honey at t .2gmlkg body weight daily and third group for oontrol. The rats ~ saaificed after four weeks o1 exposure and the lung tissues ~ processed acconingty. The sections _., stained with hemetoxyln and eosin lor neutrophil count, lmrn.~nohistochemical stain with anti-C068 and anti-C08 for macropllages and C08 T lymphocytes counts and Masson Trichrome to detemine the pathological scores. There was a significant reduction In the number ol ai1leolar maaophage in the group exposed to cigarette smoke with honey oompared to cigarette smoke exposure alone (z--2.52, p= 0.012). HoweV9f' there was no significant reduction in the nurrber ol neutrophil count (z~.54. p=0.605) and C08+ T lymphocytes counts (z--0.40, p-0.690) between the two groups and no dille~ In the pathotoglcat scores (z-1.36, p-0.892). In oonduslon, honey has a significant efrect In reducing the macrophage recruitment in airways following lnftammatory response due to dgarette smoke Inhalations. Honey also shows a redudng trend In the recruitment o1 neutrophils and C08+ T celts although It Is not statistically significant. Further researdlls needed to study the elr8ct ol honey on established aorway Inflammation In animal model.